Unusually long mRNA species coding for human alpha and beta interferons. - Sehgal, P B (1982)
Each of the several intronless interferon (IFN) alpha S genes is embedded in 4- to 5-kilobase (kb) DNA homology units which are arranged more or less in tandem in the human genome. In addition to the expected 0.8- to 1.4-kb-long IFN-alpha S mRNA species, we have detected polyadenylylated RNA molecules approximately 2-2.7, 3.5-4.5, and 7-8 kb long derived from IFN-alpha S genes in the cytoplasm of Sendai virus-induced bromodeoxyuridine-treated human lymphoblastoid (Namalwa) cells. These transcripts were detected by electrophoresis of cytoplasmic polyadenylylated RNA through agarose-CH3HgOH gels followed by blothybridization using an IFN-alpha 1 (a prototype alpha S) cDNA probe and also by translation of the eluted RNA into biologically active IFN in the Xenopus oocyte assay. At least some of these long translationally active RNA molecules appear to represent functional mRNA species because they can be detected in polysomes. In addition, the oocyte translation assay has revealed the presence of unusually long (2-8 kb) IFN-beta mRNA species both in Sendai virus-induced Namalwa cells and in poly(I) . poly(C)-induced diploid human fibroblasts (FS-4). The detection of very long IFN-alpha 1-related mRNA species suggests that some of the DNA sequence features observed in the flanking homology units may affect the transcription of the IFN-alpha S genes. Our hybridization analyses also indicate that the 1.8-kb human IFN-alpha L mRNA(s) shows no detectable cross-hybridization with an IFN-alpha 1 cDNA probe. Thus, this mRNA is derived from a gene(s) that is distinct from the IFN-alpha S set.